PEMIDANAAN TERHADAP GABUNGAN TINDAK PIDANA PENGANIAYAAN YANG MENYEBABKAN MATI DAN MENYEMBUNYIKAN KEMATIAN (STUDI KASUS PUTUSAN NOMOR 52/PID.B/2021/PN. MSH) - Mychael Haris P Sidabutar; Vientje Ratna Multiwijaya (Reformasi Hukum Trisakti, 2023)
Defendant's act of abusing the victim who did not heed the defendant's prohibition not to bathe at night, which made the defendant angry and abused the victim repeatedly, causing the victim to die and his body to be taken away. to the beach to be hidden as in Decision Number 52/Pid.B/PN. Msh. The formulation of the problem is whether the actions of the perpetrator of the crime of abuse and concealing the death of a person are in accordance with Article 338 in conjunction with Article 181 of the Criminal Code and what form the combination of criminal acts committed by the perpetrator takes. This research uses a descriptive normative type with secondary data obtained from literature study. The analysis used is qualitative by drawing deductive conclusions. The results of the research and discussion of the defendant's actions were inappropriate based on 338 of the Criminal Code in conjunction with 181 of the Criminal Code, because the perpetrator's actions did not directly result in the perpetrator's death.  The conclusion of this research is that the combined form of criminal acts committed by the perpetrator is a continuous act based on Article 64 paragraph (1) of the Criminal Code.